Toxicity of silver nanoparticles, multiwalled carbon nanotubes, and dendrimers assessed with multicellular organism Caenorhabditis elegans. (24th July 2018) - Walczynska, Marta; Jakubowski, Witold; Wasiak, Tomasz; Kadziola, Kinga; Bartoszek, Nina; Kotarba, Sylwia; Siatkowska, Malgorzata; Komorowski, Piotr; Walkowiak, Bogdan
Abstract: Nematode Caenorhabditis elegans ( C. elegans ) was used to investigate the impact of silver nanoparticles (SNP), multiwalled carbon nanotubes (MWCNT), and polyamidoamine dendrimers (PAMAM) used in concentration of 10 10 particle/mL. Population-based observations and gene expression analysis were employed in this study. SNP and PAMAM caused decrease in the number of live nematodes and their body length, but MWCNT did not affect the population of nematodes. Gene expression analysis revealed significant changes caused by the presence of all studied nanomaterials, and the results strongly suggest a specific metabolic response of the nematode organism to exposure to various nanomaterials. It was shown that C. elegans is a very sensitive organism capable to respond specifically to the exposure to some nanomaterials and therefore could be considered as a possible biosensor for early warning of presence of some nanoparticles.